Goal Pursuit in Individuals with Chronic Pain: A Personal Project Analysis - Crombez, Geert; Lauwerier, Emelien; Goubert, Liesbet; Van Damme, Stefaan (Frontiers in Psychology, 2016)
Objectives: In individuals with chronic pain (ICPs), controlling pain often is a salient goal, despite the difficulty to achieve it. This situation may bring along frustration and distress. Yet much remains unknown about the content, appraisal, and structure of goals that ICPs pursue. Here, we explore these goals, and specifically focus upon possible differences and interrelations between pain control goals (e.g., “to control my pain”) and non-pain goals (e.g., “to go to work”). Design and Methods: “Personal Project Analysis” was used in 73 ICPs (48 females; 25 males; Mage = 49.85 years; SD = 9.72) to elicit goals and goal appraisals. Interrelations between pain and non-pain goals, namely interference (i.e., negative influence), facilitation (i.e., positive influence), and necessary condition (i.e., conditional relation between pain control goal and non-pain goals) were measured with three items. Self-report measures of pain intensity, pain catastrophizing, problem solving and acceptance were completed. Results: Participants reported a variety of goals. Appraisals of pain control goals were less favorable than appraisals of non-pain goals. ICPs with higher acceptance and meaningfulness of life reported more control over pain goals, and more progress in reaching pain control goals. These individuals also reported an overall much more positive appraisal of non-pain goals (i.e., less stress, difficulty, more progress, control). In contrast, high catastrophizing and the need to solve pain were negatively related to goal appraisals. Importantly, ICP’s with high perceived meaningfulness of life despite pain experienced less necessity to achieve pain control goals in order to achieve non-pain goals. This was opposite for individuals with high levels of catastrophizing. Discussion: An understanding of why ICPs may become stuck in attempts to control their pain does not only require an understanding of how individuals appraise their pain, but also requires an understanding of how pain and non-pain goals interrelate. In particular, the view that controlling pain is necessary in order to be able to achieve other goals seems detrimental.